"Towards an index for investable security tokens": A feasibility study - Hans Christian Ohlrogge; Franz Caspar Isselstein (IU Internationale Hochschule, 2024)
Security tokens have the potential to reshape finance through blockchain technology. The Boston Consulting Group forecasts a 16 trillion opportunity in tokenizing global illiquid assets by 2030. These tokens offer transparency and efficiency in transactions, enabling fast and decentralized capital raising. However, several factors hinder rapid adoption by the buy and sell sides. Along with regulatory uncertainty, a lack of transparency and liquidity also hampers their progress. To address this, our research investigates the feasibility of creating a security token index as a benchmark for tracking their development. Our findings suggest that constructing such an index, despite certain limitations, is feasible and could provide value to various stakeholders.
Keywords: G17; G20; G30; 650; Blockchain; Security Token; Security Token Market; Security Token Indexation; Security Token Market Limitations